"Running the Gauntlet": Formidable challenges in advancing neglected tropical diseases vaccines from development through licensure, and a "Call to Action" - Maria Elena Bottazzi; Peter J. Hotez (Taylor & Francis Group, 2019)
Translational science for new biotechnologies (e.g. drugs, vaccines, devices, or diagnostics) depend on the development of a robust 'business case'. This is driven by complex scientific, technical, logistical, financial and operational elements to determine the feasibility and probability of traversing the "valleys of death" leading to licensure. The potential results in terms of profitability and financial realization, called 'product value proposition' play a crucial role in establishing incentives for investment during and after development. With this review, our goal is to summarize the challenges in taking vaccines against neglected tropical diseases (NTDs) from development through licensure and provide a perspective that these vaccines can have measurable public health and economic profitability and market success. Understanding these processes and its challenges would open the opportunity to accelerate and advance these essential NTD vaccines through the last mile towards licensure and for the delivery to afflicted populations in low- and middle-income countries.